2013
DOI: 10.1177/1474515112470056
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of patient adherence to health recommendations after acute coronary syndrome: data for targeted interventions?

Abstract: Monitoring of patient recall and adherence rate may provide information on the effectiveness of patient care management and outcomes. Identifying patients with higher risk for poor adherence is recommended for more targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The development of an effective strategy could have a powerful effect on a patient's understanding of his or her treatment and subsequent adherence to the treatment. 25,28,29 This study found that high perception of control over the disease (personal) and high perception in the influence of treatment over the CHD was associated with better adherence to medication and to increased physical activity. This result is consistent with previous studies that found that higher perceived disease control was related to better self-reported adherence to diet, medication and exercise schedule.…”
Section: Discussionmentioning
confidence: 75%
“…The development of an effective strategy could have a powerful effect on a patient's understanding of his or her treatment and subsequent adherence to the treatment. 25,28,29 This study found that high perception of control over the disease (personal) and high perception in the influence of treatment over the CHD was associated with better adherence to medication and to increased physical activity. This result is consistent with previous studies that found that higher perceived disease control was related to better self-reported adherence to diet, medication and exercise schedule.…”
Section: Discussionmentioning
confidence: 75%
“…Cognitive- and emotional-illness perceptions significantly relate to health behaviors (Platt, Green, Jayasinghe, & Morrissey, 2014; Reges et al, 2013). Appropriate health behaviors to reduce and control the risk of disease include follow-up care, medication adherence, exercise, and diet (Lee et al, 2013; Leifheit-Limson et al, 2012; Leventhal et al, 2008). The purpose of this study was to investigate health behaviors including health responsibility (health check of blood pressure and pulse, related activities, regular checkups, and medication adherence), exercise, healthy diet, stress management, and smoking cessation in patients with CAD.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Health behaviors of coronary heart disease patients decreased the risk of mortality and recurrence (Booth et al, 2014). The rate of health behaviors such as medication adherence, exercise, diet, stress management, and smoking cessation after the discharge of patients with CAD was as low as 20% to 30% (Lee, Abdullah, Bulgiba, & Abidin, 2013;Leifheit-Limson et al, 2012).…”
mentioning
confidence: 99%
“…According to the American Geriatrics Society, transitional care refers to a set of actions that is designed to ensure the coordination and continuity of health care as patients transfer between different locations or different levels of care within the same location and is often provided by interdisciplinary teams of professionals (Coleman & Boult, ). Transition from the hospital to home for patients with coronary heart disease is a vulnerable process in which several challenges can exist, such as inadequate self‐care knowledge and skills, poor medication adherence, insufficient discharge summaries that have been transmitted from hospitalists to primary care providers, and a marked increase in unplanned rehospitalizations (Lee, Abdullah, Bulgiba, & Zainal Abidin, ; Marcum et al , ; Molloy et al , ). reported that the 30 day hospital readmission rate for international patients with ST‐segment elevation myocardial infarction was 9.9% (Kociol et al , ).…”
Section: Introductionmentioning
confidence: 99%